From myth to play script: an educational project for lower secondary school students - Chiara Lanzoni (Italiano a scuola)
This paper outlines an educational experiment aimed at transforming narrative texts into theatrical scripts, with the goal of enhancing language awareness among middle school students through spoken and performed language. The project was structured in two parts (theoretical and practical): it began with the analysis of classical myths, which then were turned into a play by the students, using cooperative approach. Results, obtained through questionnaires and qualitative observations, show improvements in students’ linguistic and social skills, along with high levels of engagement in the project. Text dramatizing raised awareness of language while promoting educational inclusion and emotional well-being.